Impact of Nausea and Vomiting on Quality of Life in Cancer Patients During Chemotherapy - Roila Fausto; Ballatori Enzo (Health and Quality of Life Outcomes, 2003)
Abstract It is commonly claimed that the nausea and vomiting accompanying cytotoxic chemotherapy have a negative impact on health-related quality of life. While this may seem self-evident, until a few years ago there was little empirical data demonstrating that the failure to control postchemotherapy emesis affects aspects of quality of life. In spite of their limitations, several observational studies showed that nausea and vomiting associated with chemotherapy induced a decrease in health-related quality of life with respect to patients without nausea and vomiting. This has also been demonstrated after the adjustment for health-related quality of life before chemotherapy that is an important prognostic factor of chemotherapy-induced nausea and vomiting. Furthermore, one study suggests that the optimal time of assessment of quality of life to evaluate the impact of chemotherapy-induced nausea and vomiting is day 4 if a 3-day recall period is used or day 8 when the recall period is 7 days. In double-blind studies the efficacy, tolerability and impact on quality of life of the 5-HT3 receptor antagonists was superior with respect to metoclopramide, alizapride and prochlorperazine. Similar results have been achieved with the combination of ondansetron with dexamethasone, the standard treatment for the prevention of acute emesis induced by moderately emetogenic chemotherapy, with respect to the metoclopramide plus dexamethasone combination. Instead, in another double-blind study, in patients submitted to moderately emetogenic chemotherapy, a 5-HT3 antagonist did not seem to significantly increase complete protection from delayed emesis and the patients' quality of life with respect to dexamethasone alone. In conclusion, the evaluation of quality of life in randomized trials comparing different antiemetic drugs for the prevention of chemotherapy-induced nausea and vomiting can add important information useful for the choice of the optimal antiemetic treatment.